2020
DOI: 10.1101/2020.12.16.423023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DDI2 protease activity controls embryonic development and inflammation via TCF11/NRF1

Abstract: DDI2 is an aspartic protease that cleaves polyubiquitinated substrates. Upon proteotoxic stress, DDI2 activates the ER-bound transcription factor TCF11/NRF1 (NFE2L1), a master regulator of proteostasis maintenance in mammalian cells, and ensures the expression of rescue factors including proteasome subunits. Here we describe the consequences of DDI2 ablation both in vivo and in cells. Knock-out of DDI2 in mice resulted in embryonic lethality at E12.5 with severe developmental failure. Molecular characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 109 publications
1
4
1
Order By: Relevance
“…To further elucidate DDI2 function, we generated DDI2 deficient mice. Full body depletion of DDI2, using gene-trap technology, was embryonic lethal at middle gestational stage with decreased viability observed at E9.5 ( Figures 1 A and S1 ), confirming previous observations ( Siva et al., 2020 ). However, a DDI2 liver-specific depletion, using conditional deletion of DDI2-floxed under albumin control was viable and the toxicology results were similar to WT animals at steady state, except for catalase activity, that was reduced ( Figure S2 A).…”
Section: Resultssupporting
confidence: 90%
“…To further elucidate DDI2 function, we generated DDI2 deficient mice. Full body depletion of DDI2, using gene-trap technology, was embryonic lethal at middle gestational stage with decreased viability observed at E9.5 ( Figures 1 A and S1 ), confirming previous observations ( Siva et al., 2020 ). However, a DDI2 liver-specific depletion, using conditional deletion of DDI2-floxed under albumin control was viable and the toxicology results were similar to WT animals at steady state, except for catalase activity, that was reduced ( Figure S2 A).…”
Section: Resultssupporting
confidence: 90%
“…Our findings necessitate reconsidering the role of the DDI2/Nrf1 pathway in basal and inhibitorinduced proteasome expression. Previous studies have also reported that DDI2/Nrf1 contributes to the maintenance of basal levels of proteasomes [21,23,24] and that Nrf1 is essential for the basal proteasome expression in the brain [25], liver [26], and retina [27]; yet, in our experiments, the effects of DDI2 KO on the basal proteasome activity was not significant (Fig. 1f and S1c).…”
Section: Discussioncontrasting
confidence: 55%
“…However, in a yeast model, Ddi1 functioned as an assistant for the other shuttle factors rather than as a component 309 . DDI1 ‐deficient mice have shown no phenotypic changes compared with that of their wild type; however, in a preprint study, DDI2 deficiency in a mouse model led to developmental failure associated with early embryonic lethality 310 …”
Section: Human Phenotypes and Animal And Cellular Disease Models Asso...mentioning
confidence: 99%
“…309 DDI1-deficient mice have shown no phenotypic changes compared with that of their wild type; however, in a preprint study, DDI2 deficiency in a mouse model led to developmental failure associated with early embryonic lethality. 310…”
Section: Transport Shuttling Factorsmentioning
confidence: 99%